Rice straw, biochar and calcite incorporation enhance nickel (Ni) immobilization in contaminated soil and Ni removal capacity. (April 2020) - Ali, Umeed; Shaaban, Muhammad; Bashir, Saqib; Gao, Ruili; Fu, Qingling; Zhu, Jun; Hu, Hongqing
Abstract: Although rice straw (RS), biochar (BI) and calcite (CC) have proved to be effective immobilizing agents in acidic contaminated soil, we lack up-to-date scientific data regarding nickel (Ni) fractionation in soil and removal capacity in water. Therefore, an incubation study was undertaken to investigate the efficacy of RS, BI and CC with three application rates (0, 1 and 2%) of RS, BI and CC on the immobilization of Ni in polluted soil. Various extraction techniques were carried out: sequential extraction procedure, the European Community Bureau of Reference (BCR), extraction with CaCl2, and the toxicity characteristics leaching procedure (TCLP) techniques. Additionally, Ni sorption behavior was determined using the Langmuir and Freundlich isotherms. Results showed that adding all amendments into Ni contaminated acidic soil, enhanced soil pH, reduced the exchangeable fraction of Ni by 48%–55%, 59%–71% and 58%–66.3%, when RS, BI and CC were applied at 1% and 2% rates, respectively. According to the Langmuir adsorption isotherm results, the maximum sorption capacity was recorded using 2747 mg kg −1 in 2% CC amended soil. However, biochar exhibited the maximum Ni sorption capacity (13348 mg kg −1 ), due to its porous structure, larger surface area, and having more functional groups. Furthermore, the results of FTIR, SEM and zeta potential techniques confirmed that the immobilization and biochar's capacity to remove Ni were more effective when compared to other immobilizing agents. Highlights: Rice straw (RS) and its biochar (BI) and calcite (CC) were fabricated and applied for Ni remediation in acidic soil. BI was more effective for Ni passivation with 93.9% reduction of bioavailable Ni. Good dispersion and extra adsorption sites in BI facilitated Ni binding.